2023
DOI: 10.3389/fonc.2023.1141603
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive modulation of hepcidin in cancer and its therapeutic relevance

Abstract: Hepcidin, a short peptide synthesized primarily by hepatocytes in response to increased body iron and inflammation, is a crucial iron-regulating factor. Hepcidin regulates intestinal iron absorption and releases iron from macrophages into plasma through a negative iron feedback mechanism. The discovery of hepcidin inspired a torrent of research into iron metabolism and related problems, which have radically altered our understanding of human diseases caused by an excess of iron, an iron deficiency, or an iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 132 publications
(186 reference statements)
0
1
0
Order By: Relevance
“…b. Hepcidin: a small peptide produced by the liver that is able to induce FPN1 degradation to block iron export from cells [8]. Hepcidin is overexpressed in several human tumors, such as breast, lung and prostate cancers, as well as multiple myeloma, for its property to promote neoplastic growth by increasing iron retention in malignant cells [147]. In a breast tumor microenvironment, cancer-associated fibroblasts stimulated hepcidin expression in breast cancer cells via the production of IL-6 [148], while it has been found that hepcidin expression is associated with immune tumor infiltrates in lung cancer, particularly those constituting B cells, CD4 + T cells, macrophages, neutrophils and dendritic cells [149].…”
Section: Other Iron Proteinsmentioning
confidence: 99%
“…b. Hepcidin: a small peptide produced by the liver that is able to induce FPN1 degradation to block iron export from cells [8]. Hepcidin is overexpressed in several human tumors, such as breast, lung and prostate cancers, as well as multiple myeloma, for its property to promote neoplastic growth by increasing iron retention in malignant cells [147]. In a breast tumor microenvironment, cancer-associated fibroblasts stimulated hepcidin expression in breast cancer cells via the production of IL-6 [148], while it has been found that hepcidin expression is associated with immune tumor infiltrates in lung cancer, particularly those constituting B cells, CD4 + T cells, macrophages, neutrophils and dendritic cells [149].…”
Section: Other Iron Proteinsmentioning
confidence: 99%